CD19 and CD30 CAR T-Cell Immunotherapy for High-Risk Classical Hodgkin’s Lymphoma - Xue, YuanBo; Lai, Xun; Li, RuiLei; Ge, ChunLei; Zeng, BaoZhen; Li, Zhen; Fu, QiaoFen; Zhao, LiuFang; Dong, SuWei; Yang, JinYan; Guo, JiYin; Meng, QingYin; et al. (Frontiers in Oncology, 2021)
Background In clinical applications of CAR T-cell therapy, life-threatening adverse events including cytokine release syndrome and neurotoxicity can lead to treatment failure. Outcomes of patients treated with anti-CD30 CAR T- cell have been disappointing in relapsing/refractory (r/r) classical Hodgkin’s Lymphoma (cHL). Methods In order to understand the applicable population of multiple CAR T-cell therapy, we examined the expression of CD19, CD20, and CD30 by immunohistochemistry (IHC) in 38 paraffin-embedded specimens of cHL. In the past two years, we found only one patient with cHL who is eligible for combined anti-CD19 and CD30 CAR T-cell treatment. This patient’s baseline characteristics were prone to severe adverse events. We treated this patient with low doses and multiple infusions of anti-CD19 and CD30 CAR T-cell. Results The positive expression of CD19+ + CD30+ in Reed-Sternberg (RS) cells is approximately 5.2% (2/38). The patient we treated with combined anti-CD19 and CD30 CAR T-cell did not experience severe adverse events related to CAR T-cell therapy and received long term progression-free survival (PFS). Conclusion For high risk r/r cHL patients, low doses of CAR T-cell used over different days at different times might be safe and effective. More clinical trials are warranted for CD19 and CD30 CAR T-cell combination therapy.